A journey on the sunlit path - Ranganathan, R.; Nadkarni, Mangesh Vithal (Mirravision Trust, 2008)
Commemoration volume to Mangesh V. Nadkarni, 1933-2007, devotee of Sri Aurobindo; contributed articles